2018
DOI: 10.1016/j.mineng.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Considering the effect of pulp chemistry during flotation on froth stability

Abstract: Considering the effect of pulp chemistry during flotation on froth stability Nanji Ruth Sheni A thesis submitted to the faculty of Engineering and the Built Environment, University of Cape Town in fulfilment of the requirements for the degree of Master of Science in Engineering June 2016 I would first like to thank God who has given me the ability to will and to do His good pleasure. I would like to acknowledge and express my deepest gratitude to the following people without whom this thesis would not be possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
(101 reference statements)
1
16
0
Order By: Relevance
“…The increase of froth height with pH observed in the experiments developed in this study align with the observation of Sheni et al (2018), which observed an improvement in froth stability with pH, on the study of the froth stability in a PGM ore, using frother Senfroth 516, which is also a polyglycol frother (Ngoroma, 2015), and NaOH as the pH modifier.…”
Section: Froth Height Measurementsupporting
confidence: 89%
See 2 more Smart Citations
“…The increase of froth height with pH observed in the experiments developed in this study align with the observation of Sheni et al (2018), which observed an improvement in froth stability with pH, on the study of the froth stability in a PGM ore, using frother Senfroth 516, which is also a polyglycol frother (Ngoroma, 2015), and NaOH as the pH modifier.…”
Section: Froth Height Measurementsupporting
confidence: 89%
“…Where Vf is the froth volume, Q is the gas volumetric flow rate, Hmax is the maximum equilibrium height achieved, and A is the cross-sectional area of the column (Sheni et al, 2018;Bikerman, 1973).…”
Section: Froth Phase and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the solids and water recovery substantially decreases with increasing H2O2 dosage, which suggests that H2O2 has a significant effect on the froth stability. The Eh and pH have a strong effect on the froth phase during flotation [37] which can be altered by H2O2. To eliminate the effect of pH and Eh on the froth stability, its variation was recorded after adding H2O2.…”
Section: Flotation Performancesmentioning
confidence: 99%
“…The mass of the solids recovered to the concentrate is in the range of 14-24 g. The solids recovered are dominated by gangue minerals, rather than sulfide minerals. All batch flotation tests were done under the same The Eh and pH have a strong effect on the froth phase during flotation [37] which can be altered by H 2 O 2 . To eliminate the effect of pH and Eh on the froth stability, its variation was recorded after adding H 2 O 2 .…”
Section: Flotation Performancesmentioning
confidence: 99%